Living Donor Kidney Transplantation Should Be Promoted Among "Elderly" Patients. Issue 10 (October 2019) - Laging, Mirjam; Kal-van Gestel, Judith A.; Weimar, Willem; Roodnat, Joke I.
Abstract : Background: Age criteria for kidney transplantation have been liberalized over the years resulting in more waitlisted elderly patients. What are the prospects of elderly patients on the waiting list? Methods: Between 2000 and 2013, 2622 patients had been waitlisted. Waiting time was defined as the period between dialysis onset and being delisted. Patients were categorized according to age upon listing: <25; 25–44; 45–54; 55–64; and >64 years. Furthermore, the influence of ABO blood type and panel reactive antibodies on outflow patterns was studied. Results: At the end of observation (November 2017), 1957 (75%) patients had been transplanted, 333 (13%) had been delisted without a transplantation, 271 (10%) had died, and 61 (2%) were still waiting. When comparing the age categories, outflow patterns were completely different. The percentage of patients transplanted decreased with increasing age, while the percentage of patients that had been delisted or had died increased with increasing age, especially in the population without living donor. Within 6 years, 93% of the population <25 years had received a (primarily living) donor kidney. In the populations >55 years, 39% received a living donor kidney, while >50% of patients without a living donor had been delisted/died. Multivariable analysis showed that the influence of age, ABO blood type, and panel reactive antibodies on outflow patterns was significant, but the magnitude of the influence of the latter 2 was only modest compared with that of age. Conclusions: "Elderly" (not only >64 y but even 55–64 y) received a living donor kidney transplantation less often. Moreover, they cannot bear the waiting time for a deceased donor kidney, resulting in delisting without a transplant in more than half the population of patients without a living donor. Promoting living donor kidney transplantation is the only modification that improves transplantation and decreases delisting/death on the waiting list in this population.